2017
DOI: 10.1016/j.engfailanal.2016.11.014
|View full text |Cite|
|
Sign up to set email alerts
|

Wear behaviors and wear mechanisms of wrought magnesium alloy AZ31 fabricated by extrusion-shear

Abstract: Extrusion-Shear (ES) process for magnesium alloy is a newly developed plastic deformation technique which combines direct extrusion (DE) with ECAP(equal-channel angular pressing). Grains of ES-processed magnesium alloys can be refined effectively and mechanical properties can be improved, but the tribological properties have not been studied. In this study, the wear behaviors and wear mechanisms of AZ31 magnesium alloy samples produced by direct extrusion (DE) and extrusion-shear (ES) technologies, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It can be seen from Figure 8a,b that there were parallel furrows and a little adhesion trace on the wear trace of the AZ91D magnesium alloy, with some cracks distributing on the edge of the furrows, and some debris were observed. Hence, the wear mechanism of AZ91D was typical abrasive wear and adhesive wear [24][25][26][27].…”
Section: Wear Performancementioning
confidence: 99%
“…It can be seen from Figure 8a,b that there were parallel furrows and a little adhesion trace on the wear trace of the AZ91D magnesium alloy, with some cracks distributing on the edge of the furrows, and some debris were observed. Hence, the wear mechanism of AZ91D was typical abrasive wear and adhesive wear [24][25][26][27].…”
Section: Wear Performancementioning
confidence: 99%
“…shows the SEM micrographs of worn surfaces of annealed and ECAPed samples. Numerous studies 19,23,[54][55][56][57][58][59][60][61][62] have classified the various wear mechanisms in magnesium alloys into two basic categories of wear regimes namely, mild and severe wear regimes, based on the wear test parameters, that is, applied load and sliding velocity. In the mild wear regime exists two subregimes denoted by oxidation wear and delamination wear regime.…”
Section: Wear Studymentioning
confidence: 99%
“…For example, Niu et al have investigated the effects of test parameters such as test load, sliding speed, and ambient temperature on the friction and wear behavior of magnesium alloys and determined the wear mechanism of the Mg-3Al--0.4Si alloy under different test conditions [8,9]. Hu et al have investigated the effect of large deformation processing, such as high-pressure torsion on the tribological behavior of magnesium alloys [10,11]. Yagi et al have reported that the addition of rare earth elements such as Y and Gd can effectively enhance the wear resistance of magnesium alloys [12][13][14].…”
Section: Introductionmentioning
confidence: 99%